Differential effects of α4β7 and GPR15 on homing of effector and regulatory T cells from patients with UC to the inflamed gut in vivo. Issue 10 (24th July 2015) - Fischer, Anika; Zundler, Sebastian; Atreya, Raja; Rath, Timo; Voskens, Caroline; Hirschmann, Simon; López-Posadas, Rocío; Watson, Alastair; Becker, Christoph; Schuler, Gerold; Neufert, Clemens; Atreya, Imke; et al.
Abstract : Objective: Gut homing of lymphocytes via adhesion molecules has recently emerged as new target for therapy in IBDs. We aimed to analyse the in vivo homing of effector (Teff) and regulatory (Treg) T cells to the inflamed gut via α4β7 and G protein receptor GPR15. Design: We assessed the expression of homing receptors on T cells in peripheral blood and inflamed mucosa. We studied the migration pattern and homing of Teff and Treg cells to the inflamed gut using intravital confocal microscopy and FACS in a humanised mouse model in dextran sodium sulfate-treated NSG (NOD.Cg -Prkdcscid-Il2rgtm1Wjl /SzJ) mice. Results: Expression of GPR15 and α4β7 was significantly increased on Treg rather than Teff cells in peripheral blood of patients with UC as compared with Crohn's disease and controls. In vivo analysis in a humanised mouse model showed augmented gut homing of UC Treg cells as compared with controls. Moreover, suppression of UC (but not control) Teff and Treg cell homing was noted upon treatment with the α4β7 antibody vedolizumab. In contrast, siRNA blockade of GPR15 had only effects on homing of Teff cells but did not affect Treg homing in UC. Clinical vedolizumab treatment was associated with marked expansion of UC Treg cells in peripheral blood. Conclusions: α4β7 rather than GPR15 is crucial for increased colonic homing of UC Treg cells in vivo, while both receptors control UC Teff cell homing. Vedolizumab treatment impairs homing of UC Treg cells leading to their accumulation in peripheral blood with subsequent suppression of systemic Teff cell expansion.